Phenolics and Flavonoids Content of Wijaya Kusuma Leaves Fractions using Micro-plate Based Assay - Ni Putu Ermi Hikmawanti; Agustin Yumita; Muhammad Rafiq; Lusiana Lusiana (Indonesian Journal of Pharmaceutical Science and Technology, 2023)
Epiphyllum oxypetalum (DC.) or Wijaya Kusuma (Cactaceae) is an ornamental plant which is knownto contain polyphenol compounds. The purpose to determine the levels of total phenolic and flavonoidcompounds in the fractions of Wijaya Kusuma leaves using microplate-based assay. Each sample wasdetermined phenolic content with Folin-ciocalteu reagent and flavonoid content using AlCl3 on themicroplate. Absorption was measured using a microplate reader. Screening of DPPH radical scavengingactivity was identified using the TLC method. The results showed that the extract and fractions ofthe leaves of Wijaya Kusuma contained phenolic and flavonoid compounds. The ether fraction hadthe highest phenolic content (35,912±0,54776 mgGAE/g) and flavonoids (0,773±0,008 mgQE/g)compared to other fractions (ether>water>ethyl acetate fraction). There is one yellow spot with an Rfvalue of 0,85 in the ether fraction which is thought to be a compound capable of scavenging the DPPHradicals. The ether fraction of Wijaya Kusuma leaves has potential as a source of polyphenols withantioxidant activity. However, further research is needed to evaluate the antioxidant capacity in theether fraction of Wijaya Kusuma leaves.Keywords: Antioxidant, Epiphyllum oxypetalum (DC.) Haw, Flavonoids, Fraction, High-throughputMicroplate Assay, Phenolics.